Association Between Risk Factors Including Bone-Derived Biomarkers and Aortic Arch Calcification in Maintenance Hemodialysis Patients - Kosaku Nitta; Norio Hanafusa; Masayuki Okazaki; Mizuki Komatsu; Hiroshi Kawaguchi; Ken Tsuchiya (Karger Publishers, 2018)
Background/Aims: Aortic arch calcification (AoAC) is frequently detected in maintenance hemodialysis (MHD) patients and is associated with cardiovascular and all-cause mortality. We investigated the factors associated with AoAC and analyzed the relationship between the factors including bone-derived biomarkers and AoAC. Methods: We enrolled 389 stable MHD patients. AoAC was assessed using chest-X ray examination. Demographic data was collected in addition to serum levels of biochemical and bone-derived biomarkers, including sclerostin and fibroblast growth factor-23 (FGF-23). Results: Two hundred sixteen patients (55.5%) had AoAC. Patients with AoAC score ≥ 4 were older, with a higher percentage being male, and exhibited lower serum levels of albumin and triglyceride. Serum FGF-23 levels were inversely associated with AoAC severity, and FGF-23was directly related to vascular calcification. Age, gender, and dialysis vintage were independent predictors of AoAC. Conclusion: MHD patients have a high prevalence of AoAC. The grade of AoAC was dependent on older age in association with longer dialysis vintage. Levels of circulating FGF-23 but not sclerostin were related to AoAC severity. Serum FGF-23 levels were independently associated with AoAC.